2006
DOI: 10.1007/1-4020-4159-4_57
|View full text |Cite
|
Sign up to set email alerts
|

On the Bursting Criterion for Laminar Separation Bubbles

Abstract: Abstract:Traditionally, laminar separation bubbles have been characterised as being 'long' or 'short' on the basis of a two parameter 'bursting' criterion involving a pressure gradient parameter and Reynolds Number at separation. In the present work we suggest a refined bursting criterion, which takes into account not just the length of the bubble but also the maximum height of the bubble, thereby shedding some light on the less understood phenomenon of 'bursting' in laminar separation bubbles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The process through which a short bubble suddenly fails to reattach and becomes a long bubble after a small variation in angle of attack or Reynolds number is referred to as bursting. Its physical causes and the determination of an adequate criterion for predicting its occurrence are still today an active topic of research (Gaster 1967;Pauley, Moin & Reynolds 1990;Diwan, Chetan & Ramesh 2006;Marxen & Henningson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The process through which a short bubble suddenly fails to reattach and becomes a long bubble after a small variation in angle of attack or Reynolds number is referred to as bursting. Its physical causes and the determination of an adequate criterion for predicting its occurrence are still today an active topic of research (Gaster 1967;Pauley, Moin & Reynolds 1990;Diwan, Chetan & Ramesh 2006;Marxen & Henningson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The process in which a short bubble suddenly fails to reattach and becomes a long bubble after a small variation on angle of attack or Reynolds number is referred to as bursting; 4 its physical causes and the determination of an adequate criteria for predicting its occurrence have been since the 60's, and are still today, an active topic of research. [4][5][6][7][8] The usual picture of inviscid instability of the separated shear layer leading to laminar-turbulent transition, and turbulent mixing being ultimately responsible for the reattachment of the separation bubble suggested considering the properties of the boundary-layer at separation as a criterion for bursting. Besides bursting, the prediction of other characteristics of separated flow like the onset of unsteadiness (sometimes associated directly with bursting 6 ) or three-dimensionalization of nominally two-dimensional laminar separation bubbles 9,10 has been attempted through the study of linear instability mechanisms of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…This was contradicted by Schmidt & Mueller 19 , who concluded that at low Reynolds number situations the laminar part of the bubble had a very important influence on the flow development. Diwan et al 20 proposed a refined bursting criterion, which takes into account not only the length of the separation bubble but also the maximum height, as it was argued that the transition to turbulence was initiated roughly at a streamwise location corresponding to the maximum height. Their refined non-dimensional pressure gradient parameter is given as…”
Section: Section View Of a Laminar Separation Bubble (From Mayle 31 )mentioning
confidence: 99%